Developing your conflict competence : a hands-on guide for leaders, managers, facilitators, and teams - Runde, Craig E., 1951-; Flanagan, Tim A., 1955-; Center for Creative Leadership (San Francisco : Jossey-Bass, 2010)
"Developing Your Conflict Competence is a practical book that offers a hands on resource for leaders, managers, team members, and everyone within an organization who wants to sharpen their skills and learn to respond to conflict with confidence. This third book in the "conflict competent" series is filled with tips, checklists, exercises, and illustrative stories that offer insight into the nature of conflict and show how to handle conflict successfully." "Throughout the book, authors Craig Runde and Tim Flanagan outline a concrete process for dealing with unavoidable workplace tensions and present a series of thought-provoking questions and self-diagnostics. Developing Your Conflict Competence is a comprehensive guide to managing disagreements, differences, and discord. It shows how an individual can practically help others deal with conflicts that are causing friction within an organization. Runde and Flanagan also give down-to-earth advice for dealing with discord within teams. They show how teams can establish norms for handling conflict by creating the right climate for discussing issues and using effective communication techniques. On a more global level, the authors present specific approaches for changing organizational culture so conflict can be addressed with effectiveness and immediacy."--BOOK JACKET.
Cognitive aspects of conflict -- The emotional side of conflict -- Engaging conflict constructively -- Team conflict competence -- Organizational conflict competence.
"A joint publication of the Jossey-Bass business & management series and the Center for Creative Leadership."
Includes bibliographical references and index.
Keywords: Conflict management; Interpersonal conflict